Developing the GEN-V Startup Ecosystem: An AI-Driven Integration of Multidisciplinary Learning in Vocational High School - Ali Basyah; Waras Kamdi; Purnomo Purnomo; Tuwoso Tuwoso; Razali Hassan (International Journal of Educational Narratives, 2026)
Background. Traditional vocational education often operates in “silos,” where subjects are taught in isolation, hindering students' ability to integrate diverse competencies into real-world work scenarios. Purpose. This study develops and evaluates the “GEN-V” startup ecosystem an innovative pedagogical model designed to integrate 13 subjects through an AI-driven digital startup project for vocational high school students. Method. Utilizing a Research and Development (R&D) approach with the ADDIE model, this study involved 95 students from three classes (XII DKV 1, 2, and 3) at SMK Negeri 1 Mojokerto, organized into 18 startup teams. Each team was structured into six specialized roles: Chief Executive Officer (CEO), Chief Product Officer (CPO), Chief Marketing Officer (CMO), Chief Financial Officer (CFO), Chief Technology Officer (CTO), and Chief Content Officer (CCO). Data were collected through a centralized project management dashboard, an 8-week startup sprint observation, and multidisciplinary evaluations from a panel of 14 teacher-mentors. Results. The findings demonstrate that the GEN-V ecosystem effectively synchronized multidisciplinary tasks. The “Traffic Light” monitoring system evidenced a 95% task completion rate across all specialized departments. Furthermore, the strategic integration of Google Gemini AI significantly accelerated content production and financial modeling, enabling teams to achieve realistic Break-Even Point (BEP) projections and market validation within a condensed timeframe. Conclusion. The GEN-V ecosystem serves as a transformative learning model that successfully dismantles subject barriers. By fostering AI-human collaboration and disciplined project management, it effectively prepares vocational students for the complexities of the digital startup industry.